PELAKSANAAN PROMOSI KESEHATAN RUMAH SAKIT DI RSU HAJI SURABAYA - Adi Larasanti (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2017)
Health Promotion is an eff ort to empower communities to maintain, improve and protect their own health and environment. Hospital Health Promotion (PKRS) targeting patients, community, hospital and the surrounding environment is a program implemented at RSU Haji Surabaya to obtain accreditation. The purpose of PKRS at Rumah Sakit Umum Haji Surabaya is to develop patient and family understanding of the illness suff ered as well as the things that his family needs to do, in assisting healing and preventing reinfection by the same disease. If implemented properly, PKRS can contribute greatly to improving the quality and image of health services in Indonesia, especially RSU Haji Surabaya. This research is a qualitative analysis research with descriptive approach to analyzehealth promotion in Rumah Sakit Umum Haji Surabaya by conducting in depth interview with research respondents. The research results of Analysis Hospital Health Promotion of Rumah Sakit Umum Haji Surabaya Based on the Peraturan Menteri Kesehatan Republik Indonesia Nomor 004 Tahun 2012, the result that the use of electronic media has not been delivered, advocacy activities tend not to run and the partnership aspect has not reached the large scale private sector. In this research, it can be concluded that the implementation of hospital health promotion in Rumah Sakit Umum Haji Surabaya has not been running maximally so that the participation of the Board of Directors, the community and all employees of Rumah Sakit Umum Haji Surabaya are needed. If the health promotion program runs well then it will aff ect the level of people satisfaction.Keywords: Hospital Health Promotion, RSU Haji Surabaya